2015
DOI: 10.1016/j.apjtm.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of garlic oil extract on Schistosoma mansoni infected mice

Abstract: Results obtained confirmed the effect of garlic oil extract on the larval and mature stage of the parasite and in enhancing the host's immune system against the disorders caused by S. mansoni in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Additionally, the obtained results showed that both allicin levels improved serum immunoglobulins (IgG and IgM), as immunity markers, while decreased lipid peroxidation marker (TBARS), showing the highest improvement of immunity and lipid peroxidation of does with allicin at a level of 10 mg per kg BW (Table ). In accordance with the present results, allicin as a vital compound in garlic exerted positive impact on immunity of young animals (Wang et al, ), broiler chicken (El‐Katcha et al, ) and infected animals through increasing of immunoglobulins levels (Kamel & El‐Shinnawy, ). In rabbits, allicin treatment increased serum IgG and IgM levels in blood (Alam et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the obtained results showed that both allicin levels improved serum immunoglobulins (IgG and IgM), as immunity markers, while decreased lipid peroxidation marker (TBARS), showing the highest improvement of immunity and lipid peroxidation of does with allicin at a level of 10 mg per kg BW (Table ). In accordance with the present results, allicin as a vital compound in garlic exerted positive impact on immunity of young animals (Wang et al, ), broiler chicken (El‐Katcha et al, ) and infected animals through increasing of immunoglobulins levels (Kamel & El‐Shinnawy, ). In rabbits, allicin treatment increased serum IgG and IgM levels in blood (Alam et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that this mechanism of action is made by enhancing the immunity of the host to attack the parasite (EL-Shenawy et al, 2008). It is also thought that the antioxidative properties of both AGE and GOE have strong effects in Schistosoma infected mice (EL-Shenawy et al, 2008;Kamel and El-Shinnawy, 2015;El-Kott et al, 2011). The development of eggs are continued in the tissue until maturation, then until the time of death, the mature ova are remained alive in the tissue.…”
Section: In Vivo Studiesmentioning
confidence: 94%
“…As one milliliter of aqueous extract contained 660 mg of garlic Materials (Sener et al, 2006). To obtain GOE, distillation method was used according to method described by Kamel and El-Shinnawy, (2015).…”
Section: Preparation Of Garlic Extractsmentioning
confidence: 99%
“…They showed that total IgG of the S. mansoni infected patients was elevated in the range of two to three times above normal. Also, mice infection with S. mansoni showed a significant (P<0.001) increase in serum IgG as compared to normal control (Kamel and El-Shinnawy, 2015). In addition, El-Sisi et al (2011) reported that mice infected with Schistosoma mansoni live cercariae showed a time-dependent increase in serum IgE, IgG levels compared with the control group.…”
Section: Discussionmentioning
confidence: 95%